Rectangular microstrip antenna with dumbbell shaped defected ground structure for improved cross polarised radiation in wide elevation angle and its theoretical analysis. Issue 1 (1st January 2016) - Ghosh, Abhijyoti; Chakraborty, Subhradeep; Chattopadhyay, Sudipta; Nandi, Arnab; Basu, Banani
Abstract : A simple and compact rectangular microstrip patch antenna (RMPA) with dumbbell shaped defected ground structure has been proposed and investigated experimentally for significant suppression of cross polarised (XP) radiation compared with maximum co‐polarised gain without affecting the co‐polarised radiation pattern. The investigation shows that the proposed antenna has an excellent co‐polarised radiation to XP radiation isolation over wide elevation angle around the broadside for different aspect ratio (width to length ratio or W/L ) of RMPA. The proposed idea is justified in the light of concrete theoretical analysis.